Integrated molecular pathology: the Belfast model. Issue 12 (December 2015) - Salto-Tellez, Manuel; Kennedy, Richard D.
Highlights: Clinical outcomes are the measure of quality in science. Much of the failure in biomarker discovery and validation is related to the way we understand and deliver molecular pathology activities. The current model for cancer discovery and treatment is not sustainable. An integrated model for molecular pathology provision is likely to overcome some of the existing barriers in biomarker validation and adoption.